High-efficiency ZOGAN blue micro-LEDs with superior thermal-stress reliability for ultra-high-resolution displays - Dong-Min Jeon; Sung-Ki Hong; Yung Ryel Ryu; Jong Hyeob Baek; Dong-Soo Shin; Jong-In Shim (AIP Advances)
Visible light-emitting-diode (LED) chips suffer from a problem called size-dependent droop (S-droop), which causes a decrease in external quantum efficiency (EQE) when the chip size decreases below a few tens of micrometers. The device reliability also degrades with the chip-size reduction. To address this issue, we have fabricated blue micro-LEDs with a ZnO layer (ZOGAN micro-LED). The device mesa structures measure 5–20 μm in diameter with a highly As-doped p-type ZnO layer additionally deposited onto a conventional epitaxial structure of a blue LED grown on a sapphire substrate. Experimental results show that the leakage current at the sidewall is effectively suppressed, and devices with diameters of 5, 10, and 20 μm achieve similar EQE peak values of ∼50%. Moreover, the device with a diameter of 5 μm is demonstrated to have a small thermal degradation (T-droop) even at high temperatures of 400 K. From the spectral analysis, it is inferred that this superior performance is due to strain relaxation occurring in the active quantum wells, which enhances radiative recombination without any further increase in the nonradiative recombination rate.